Chaffin, Sea Of Gray - The Around-The-World Odyssey Of The Confederate Raider Shenandoah - Gudmestad, Robert (Teaching History: A Journal of Methods, 2006)
On October 8, 1864, the Sea King slipped down the Thames River and sailed into the Atlantic Ocean. The ship arrived at the island of Las Desertas, where it took on supplies. It also revealed its true name, the CSS Shenandoah. A Confederate commerce raider in the style of the CSS Alabama and Florida, the mysterious ship had orders to attack Yankee whaling ships in the Bering Sea.